Detrimental effect of systemic antimicrobial CD4+ T‐cell reactivity on gut epithelial integrity. Issue 2 (25th November 2016) - Kwong Chung, Cheong K.C.; Ronchi, Francesca; Geuking, Markus B.
Summary: Healthy host–microbe mutualism relies on compartmentalization and proper regulation of systemic and mucosal immune responses. Nevertheless, the systemic immune system is frequently exposed to bouts of bacteraemia, which can trigger systemic antimicrobial immune reactivity including CD4 + T cells. Low‐level bacteraemia can occur when immune compartmentalization is compromised, for example in the presence of innate immune deficiency or following use of non‐steroidal anti‐inflammatory drugs. We generated an Escherichia coli strain expressing a defined T helper neo‐epitope to study systemic antigen‐specific antimicrobial CD4 + T cells and their potential involvement in the pathogenisis of inflammatory bowel diseases. We found that the dose of bacteria required for the induction of systemic antimicrobial CD4 + T‐cell proliferation was high and not easily reached under physiological conditions. Importantly, however, when intestinal barrier function was compromised by induced damage to the intestinal epithelium, the presence of systemic antimicrobial CD4 + T cells specific for a single neo‐antigen resulted in dramatically increased levels of bacterial translocation. This study therefore demonstrates that systemic antimicrobial CD4 + T‐cell reactivity might impact adversely on the mucosa under conditions of reduced barrier function and that despite strong mucosal immune regulation, antigen‐specific recognition is still sensitive. Abstract : This study demonstrates that systemic antigen‐specific antimicrobial T‐cell reactivity impacts on the mucosa. This is important in the context of inflammatory bowel diseases. Furthermore, this is the first study demonstrating the impact of antigen‐ and species‐specific CD4 T‐cell reactivity.